Let f(x)=x^x for x>0, then find f'(x) for all x>0.

A common misconception from many students when tackling this problem is that they think the usual 'power rule' works. However, in this case the power is itself a function of x and not just a constant, so this would not work. To solve this problem, we will have to 'get rid' of the power. We will do this using the natural logarithm. ln(f(x))=xln(x) (1)Differentiating (1) and using the product rule on the right hand side and the chain rule on the left hand side, we get f'(x)/f(x)=ln(x)+1 Lastly rearranging for f'(x) and substituting for f(x), we derived f'(x)=x^x ( ln(x)+1) as required. This technique is known as logarithmic differentiation.

Related Further Mathematics A Level answers

All answers ▸

Solve x^3=1 giving all the roots between -pi<=theta<=pi in exponential form


For a homogeneous second order differential equation, why does a complex conjugate pair solution (m+in and m-in) to the auxiliary equation result in the complementary function y(x)=e^(mx)(Acos(nx)+Bisin(nx)), where i represents √(-1).


Find the solution the the differential equation d^2y/dx^2 + (3/2)dy/dx + y = 22e^(-4x)


Find y in terms of x for the equation 2x(dy/dx) + 4y = 8x^2


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences